2021
DOI: 10.1016/j.carres.2021.108326
|View full text |Cite
|
Sign up to set email alerts
|

Marine sulfated polysaccharides as potential antiviral drug candidates to treat Corona Virus disease (COVID-19)

Abstract: The viral infection caused by SARS-CoV-2 has increased the mortality rate and engaged several adverse effects on the affected individuals. Currently available antiviral drugs have found to be unsuccessful in the treatment of COVID-19 patients. The demand for efficient antiviral drugs has created a huge burden on physicians and health workers. Plasma therapy seems to be less accomplishable due to insufficient donors to donate plasma and low recovery rate from viral infection. Repurposing of antivirals has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 222 publications
0
42
0
2
Order By: Relevance
“…Many studies have reported that sulfated polysaccharides are good protective agents for antioxidant enzymes in cells. Thus, the sulfate content and molecular weight of sulfated polysaccharides will have a certain impact on the antioxidant activity ( Andrew and Jayaraman, 2021 ). Sun et al (2018) indicated that Laminaria japonica polysaccharides with a higher content of sulfuric acid groups and a smaller molecular weight have a strong ability to scavenge free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported that sulfated polysaccharides are good protective agents for antioxidant enzymes in cells. Thus, the sulfate content and molecular weight of sulfated polysaccharides will have a certain impact on the antioxidant activity ( Andrew and Jayaraman, 2021 ). Sun et al (2018) indicated that Laminaria japonica polysaccharides with a higher content of sulfuric acid groups and a smaller molecular weight have a strong ability to scavenge free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 exhibits several complications, such as lung damage, blood clot formation, respiratory illness, organ failures [ 49 ], and neurologic manifestations such as taste [ 50 ] and smell loss [ 51 ] in most patients. At present, there is no report available for anticoronavirus activity of both lignosulfonate and sulfated polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no report available for anticoronavirus activity of both lignosulfonate and sulfated polysaccharides. Since these substances prevent virus entry into host cells, they can be used as candidate drugs, adjuvants in vaccines, or in combination with other antivirals, antioxidants, and immune-activating nutritional supplements and antiviral materials to prevent SARS-CoV-2 infection [ 49 ]. The anti-diabetic [ 8 ], anti-inflammatory [ 9 ], and antiviral activity (this study) of lignosulfonate, and the neuroprotective activity of lignin [ 52 ] and SE [ 53 ] may be advantageous for the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Other enveloped viruses affected by carrageenans included dengue virus type 2 (DENV-2) [ 8 , 39 , 69 ], human immunodeficiency virus (HIV) [ 63 , 70 ], Sindbis virus [ 63 ], Influenza virus (IAV) [ 16 ], human metapneumovirus (HPNV) [ 11 ], porcine reproductive and respiratory syndrome virus (PRRSV) [ 25 ], rabies virus (RABV) [ 46 ], Rift Valley fever virus (RVFV) [ 67 ], vaccinia virus [ 62 , 63 ], Semliki forest virus and swine fever virus [ 62 ], hantaviruses [ 71 ], and the fish virus viral haemorrhagic septicaemia virus (VHSV) [unpublished results]. In addition, recent studies have demonstrated that iota and lambda carrageenans have a potent inhibitory activity against SARS-CoV2 [ 61 , 72 , 73 ], and other sulfated polysaccharides have been postulated as candidates for prevention and/or treatment of the COVID-19 [ 36 , 74 , 75 ]. Some authors have also reported activity against non-enveloped viruses such as human rhinovirus (HRV) [ 76 ], enterovirus 71 (EV-71) [ 24 ], and papillomavirus type 16 (HPV-16) [ 77 ].…”
Section: Mechanisms Of Antiviral Activitymentioning
confidence: 99%